Karakteristik dan Analisis Keindahan Syair Lisanuddin Ibnu al-Khathib - Kaltsum, Ummu; Nuruddin, Ahmad; Dzulhijjah, Siti Khoirotin (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2024)
Lisanuddin Ibnu al-Khatib is one of famous poets in his period. Besides of his famous poet status, he was also a good writer, sword expert, good archer and a scholar. He had organized a lot of literary works include poetry, history, geography, etc. Hence, this paper would like to explain more about his biography and literary works whose aim to understand his literary works characteristics. In this case, we, the writers use descriptive analyzing towards his works which then clarify the data of analysis got from learning and understanding his poetry and other literary works of him. One the example of his works is “fī layālin katamat sirr al-hawā # fī al-dujā laulā syumūs al-gurarī”. The writers identify the use of “Balāgah” elements such as: kināyah, tasybīh mursal mufaṣṣal, jinās gairu tām, isti’ārah taṣrīḥīyah. Briefly, Lisanuddin also apply the elements of Arūḍ wa al-Qawāfī. In addition, the most obvious characteristics of his literary works is that he uses easy words in order the reader easily understand his works.